Index of the use of paper per student at UNHEVAL - 2011 - Hilario-Cárdenas, Jorge R. (2019)
The goal of this research was to determine the índex of use of paper per student at Hermilio Valdizan National University in 2011, since there is no information about this and it is necessary to count with it, since it is importantto have with a tool forenvironmental management. Forthe development of this study a sample from the student population enrolled in the academic year 2011 was determined; sampling resulted in sub-samples that were formed on the basis of the number of students from each Academic Professional School of the main headquarters of the University. For the data collection, an instrument (survey) was used which was validated by the research group and subsequently determined its reliability through a pilot group of students. The development of the work allowed us to comply with the general objective, and as a result of this we have that each student at UNHEVAL uses on average 951 sheets of bond per year and, if this result we make depending on the raw material required for the production of paper - in this case the trees - to satisfy this need is necessary the felling of 503 trees of 15 years oíd. This result indícate us that the University as an entity generator of knowledge and development, must also be the pioneer in taking action to reduce the use of paper in this institution and does not form part of being a generator of contamination and degradation of ourenvironment.